Faktor-Faktor Yang Mempengaruhi Keputusan Wisatawan Domestik Berkunjung Ke Bali Safari & Marine Park, Gianyar Bali - Pranata, Nyoman Indra; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 2 No 8 (2013), 2013)
Bali Safari & Marine Park offers amusement parks are spacious and comfortable with a theme like a wild forest and on the African continent Promotion and service factors with eigen value of 5.541, the environment and personal factors had eigen value of 5,450, the psychological factor eigen value of 4.790, the price factor has eigen value of 4.614, the product of factors have eigen value of 1.644 and a reliability factor has eigen value of 1,345. Whereas variables representing each of the factors that influence the decision of domestic tourists visiting Bali Safari & Marine Park variable electronic media with 0.904 factor loading, peer variables with factor loading 0.926, belief variables with factor loading 0.915, variable BSMP facility with 0.886 factor loading, variable types of entertainment and games with variable loading factor 0.824 and hospitality employees with 0.812 factor loading. Dominant factors that influence the decision of domestic tourists visiting Bali Safari & Marine Park, Gianyar Bali is the service factor to the largest eigen value 5.541 . Keywords: Factor analysis, decision travelers